Sustainable development in potiguar semiarid coast: the process of consolidation of reserva de desenvolvimento sustentável estadual Ponta do Tubarão in Macau/RN and Guamaré/RN - Nóbrega, André Elias de Oliveira; Musse, Narla Sathler de Oliveira (Geosaberes, 2019)
The exploitation of natural resources in an unsustainable way and the increasing rhythm of consumption of the world population have caused numerous social and environmental problems. Thus, the need arises to plan and elaborate conservation strategies such as the creation and management of Conservation Units (CUs). In this sense, this article aims to present the process of consolidation of the Reserva de Desenvolvimento Sustentável Estadual Ponta do Tubarão (RDSEPT), located between the municipalities of Macau and Guamaré, on the northern coast of the State of Rio Grande do Norte. The discussions were structured based on the articulation of the concepts of Sustainable Development and Environmental Education, through which are also presented the main economic activities developed there and the measures elaborated to promote awareness and environmental awareness in the local community. To do so, we used a qualitative approach, in which the data collection tools were: the bibliographic research and the field study. Finally, it was concluded that RDSEPT is a living example of a sustainable community, especially the role played by the local population in the conservation of ecosystems and biomes present in the Reserve, as well as the maintenance of traditional over the years.